Media Buku Saku Berbasis Motorik Halus untuk Anak Pra-Sekolah - Wulan Patria Saroinsong; Winda Afni Farikhah (Universitas Al-Hikmah Indonesia, 2020)
Research on the development of the Fine Motor Pocket Book media has a goal that is, to determine the results of the development of a pocket book and to get the effectiveness of a fine motor pocket book. This research method uses the type of R&D or research and development with ADDIE development models. The trial design used in this study used the Survey method. The targets in this study are 50 parents and 50 kindergarten / RA teachers in Surabaya who have children aged 4-5 years. Data was obtained and collected using a questionnaire technique that was carried out online through Google forms, and documentation techniques in the form of product designs before and after revision. The results of this study are the Fine Motor Pocket Book media. The survey results and feedback from teachers and parents showed that the fine motor pocket book that was developed proved to be very valid. this is shown through the material or media in the pocket book, the level of explanation in the picture / text 3.07, the level of suitability of the location has a mean value of 3.28, the level of quality of the book has a value of 3.15 which means 51-75 responses of teachers and people old is very effective. Furthermore, the attractiveness and suitability of the location of 3.28 and the level of accuracy has a mean value of 3.35 where the value approaches a score of 4, which means 76-100 means effective. These results can be categorized very well so that it is feasible and effective to be used in learning at school or at home. The results of this fine motor pocket book research have implications on the development of fine motor aspects in children.